Managing Dynamic Context to Enable User-Driven Web Integration in the Personal Web (2010)
The Personal Web is the people-centric instan-tiation of the Smart Internet where informa-tion systems, services and web content are ar-ticulated by users according to their matters of concern. To realize the vision of the Per-sonal Web, the Smart Internet requires infras-tructure to support the user in the integra-tion of personal data and the composition of personal services within a highly dynamic con-text that constitutes the user's Personal Web Sphere. To address these requirements, we pro-pose a user-driven context management frame-work, built on the top of the basic enabling infrastructure of the Personal Web, to support users in the run-time modification of personal context models. The core of our proposal is the management of monitoring concerns by imple-menting feedback loops, where the user acts as the planner of the controller to adapt the mon-itoring strategy by means of using web inter-actions to modify the personal context models. These context models, deployed at three differ-ent levels of abstraction, represent monitoring concerns by defining abstract types of contex-tual entities, the relationships among them and the interactions that the user can instantiate to drive web integration.